Isolated in academia : an analytical study of the mechanisms of academic boycotts - McKenzie, Megan J. (Irish School of Ecumenics, 2006)
Academic boycotting is withdrawing support for or participation in one or more aspects of academia in order to make specific changes. Support is restored after those who are boycotted make the desired changes. The mechanisms of academic boycotts are poorly understood, and thus, they tend to be used indiscriminately and ineffectively. This thesis argues that the sole function of academic boycotting is to create the conditions required for functional discussion after an impasse is caused by non-existent or failed discussion. As a powerful and coercive instrument for change, boycotts are blunt and thus incapable of transmitting complicated ideas, dealing with multifaceted problems or delicate nuances, or engaging in interactive dynamic negotiation. However they can increase factors, such as awareness or reasons to engage, which are required in order for discussion to be fruitful. This makes them particularly suited to surfacing types of latent conflict that are often insufficiently addressed in academia. Consequently, while academic boycotts alone cannot realise complex goals directly, the resulting discussion may be able to achieve such goals.
Keywords: Ecumenics, Ph.D.; Ph.D. Trinity College Dublin